Physical Measurement of Ice Jams 1976-77 Field Season. - Wuebben,James L; Stewart,Douglas M (1978)
Three shallow stream ice jams which occured on the Ottauquechee River in Vermont during the 1976-77 winter season are documented. Measurements of the variation in jam thickness along the longitudinal profile of the jams are given along with the variation in surface ice flow sizes. These measurements are compared with those of previous work. All jams were caused to some extent by backwater conditions in the river. The effects of an ice cover and the ice jams on the longitudinal water surface profiles are examined and compared with open water conditions. (Author)